Case studies in knowledge management - Jennex, Murray E. 1956- (Hershey, PA Idea Group Pub., 2005)
Case Studies in Knowledge Management provides case-based lessons learned from several examples of actual applications of knowledge management in a variety of organizational and global settings. A variety of KM issues are explored, including issues associated with building a KMS, organizational culture and its effect on knowledge capture, sharing, re-use, strategy, and implementation of KM initiatives and a KMS. The benefit of focusing on case and action research is that this research provides an extensive and in-depth background and analysis on the subjects, providing readers with greater insight into the issues discussed.
Chapter I. Learning from simple systems : the case of JPL 101 / Lynne P. Cooper, Rebecca L. Nash, Tu-Anh T. Phan, Teresa R. Bailey -- Chapter II. A knowledge management case study in developing, documenting, and distributing learning / Brigette McGregor-MacDonald -- Chapter III. A case study on assessing the readiness of professional services company to build an organizational memory information system / Hani Abdel-Aziz, Khaled Wahba -- Chapter IV. Rebuilding core competencies when a company splits : a case study of assessing and rebuilding expertise / Gail Corbitt -- Chapter V. Exploring the impacts of knowledge (re)use and organizational memory on the effectiveness of strategic decisions : a longitudinal case study / Afsoun Hatami, Robert D. Galliers -- Chapter VI. Governance of strategies to manage organizational knowledge : a mechanism to oversee knowledge needs / Suzanne Zyngier, Frada Burstein, Judy McKay -- Chapter VII. Challenges in developing a knowledge management strategy for the air force material command / Summer E. Bartczak, Ellen C. England -- Chapter VIII. Knowledge management in a project climate / Elayne Coakes, Anton Bradburn, Cathy Blake -- Chapter IX.Where knowledge management resides within project management / Jill Owen, Frada Burstein -- Chapter X. Organizational knowledge sharing based on the ERP implementation of Yongxin Paper Co., Ltd / Zhang Li, Tian Yezhuang, Li Ping -- Chapter XI. Supporting research and development processes using knowledge management methods / Thomas Hahn, Bernhard Schmiedinger, Elisabeth Stephan -- Chapter XII. ̃CoM : decentralized knowledge management systems for cooperating ̃- and mold-making SMEs / Florian Bayer, Rafael Enparantza, Ronald Maier, Franz Obermair, Bernhard Schmiedinger -- Chapter XIII. Reserve bank of New Zealand : journey toward knowledge management / Yogesh Anand, David J. Pauleen, Sally Dexter -- Chapter XIV. A comparative case study of knowledge resource utilization to model organizational learning / Colin White, David Croasdell -- Chapter XV. Implementing knowledge-enable CRM strategy in a large company : a case study from a developing country / Minwir Al-Shammari -- Chapter XVI. Why knowledge management fails : lessons from a case study / Ivy Chan, Patrick Y. K. Chau -- Chapter XVII. Infosys technologies, limited / Nikhil Mehta, Anju Mehta -- Chapter XVIII. Keeping the flame alive : sustaining a successful knowledge management program / Eliot Rich, Peter Duchessi -- Chapter XIX. Knowledge management for healthcare : using information and communication technologies for decision making / A. N. Dwivedi, Rajeev K. Bali, R. N. G. Naguib -- Chapter XX. Productivity impacts from using knowledge / Murray E. Jennex.
Includes bibliographical references and index.
Keywords: Knowledge management -- Case studies; Electronic books